Gender and Top Lifetime Earnings Inequality: Ten New Facts from Brazil - Tomás R. Martinez; Antonio Martins-Neto; Ursula Mello (Institute of Labor Economics (IZA), 2025)
This paper presents ten new facts on gender and top lifetime earnings inequality in Brazil, drawing on rich administrative data covering nearly the entire formal labor market from 1985 to 2018. We document significant gender disparities in lifetime earnings, particularly among top earners, where women are both underrepresented and face larger earnings gaps compared to men. We identify key drivers of this inequality, including labor force participation, occupational segregation, employment in large firms, and job-switching patterns. Public sector employment partially mitigates these gaps.
Keywords: D33; J01; J30; J45; 330; life cycle earnings inequality; gender earnings gap; top earners